2021
DOI: 10.1080/00423114.2021.1962537
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of the equivalent conicity function's nonlinearity on the dynamic behaviour of a rail vehicle under typical service conditions

Abstract: Generally, the equivalent conicity function (ECF) is denoted by equivalent conicity at 3mm (λ 3mm ) and a Nonlinearity Parameter (NP). NP describes the nonlinearity of the ECF and its influence on a vehicle design is explored thoroughly, however, NP's role in vehicle and track maintenance is not researched yet. This paper investigates the influence of track maintenance actions on vehicle dynamics with help of NP vs λ 3mm scatter plots of ECF database. The ECF database is constructed by combining measured worn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Finding an optimal solution should also consider the timetable, passenger comfort, traffic conditions on the route, and the durability and reliability of rail vehicles. This analysis serves as a starting point for further work on the energy efficiency of electrified rail transport, aiming to develop an energy optimisation algorithm [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding an optimal solution should also consider the timetable, passenger comfort, traffic conditions on the route, and the durability and reliability of rail vehicles. This analysis serves as a starting point for further work on the energy efficiency of electrified rail transport, aiming to develop an energy optimisation algorithm [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind the long-life cycle of railway vehicles, it is of the utmost importance that individuals in charge of this process possess proper knowledge and base their decisions on precise factors [8][9][10].…”
mentioning
confidence: 99%
“…Finally, the results suggested that the wheel re-profiling distance of the high-speed trains should be controlled between 160,000 km and 200,000 km. Kulkarni et al 10 used the NP value to study the measured rail profile and wheel profile matching in different zones. The NP value of 3 mm must be considered in track maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Polach’s approach showed that the nonlinearity of the equivalent conicity had the most effect on the bifurcation, whether it was subcritical or supercritical. 11,12 Kulkarni et al 13 examine the effect of track maintenance on vehicle dynamics as supported by the nonlinearity parameter and the equivalent conicity at 3 mm on Swedish Railway. Li et al 14 studied the effect of track parameters on wheel–rail contact and carbody hunting stability.…”
Section: Introductionmentioning
confidence: 99%